The Effects of Lutein and Zeaxanthin Supplementation on Cognitive Function in Adults With Self-Reported Mild Cognitive Complaints: A Randomized, Double-Blind, Placebo-Controlled Study - Lopresti, Adrian L.; Smith, Stephen J.; Drummond, Peter D. (Frontiers in Nutrition, 2022)
Background: Lutein and zeaxanthin are fat-soluble, dietary carotenoids that have high concentrations in human brain tissue. There have been several studies confirming an association between lutein and zeaxanthin and cognitive function. Purpose: Examine the effects of lutein and zeaxanthin supplementation on cognitive function in adults with self-reported cognitive complaints. Study Design: Two-arm, parallel-group, 6-month, randomized, double-blind, placebo-controlled trial. Methods: Ninety volunteers aged 40 to 75 years received either 10 mg of lutein and 2 mg of zeaxanthin, once daily or a placebo. Outcome measures included several computer-based cognitive tasks, the Cognitive Failures Questionnaire, Behavior Rating Inventory of Executive Function, Profile of Mood States, and the Patient-Reported Outcomes Measurement Information System-29. Results: Compared to the placebo, lutein and zeaxanthin supplementation was associated with greater improvements in visual episodic memory (p = .005) and visual learning (p = .001). However, there were no other significant differences in performance on the other assessed cognitive tests or self-report questionnaires. Lutein and zeaxanthin supplementation was well-tolerated with no reports of significant adverse effects. Conclusion: The results from this trial suggest that 6-months of supplementation with lutein and zeaxanthin may improve visual memory and learning in community-dwelling adults with self-reported cognitive complaints. However, it had no other effect on other computer-based measures of cognitive performance or self-report measures of cognition, memory, mood, or physical function.